2006
DOI: 10.1191/1358863x06vm678oa
|View full text |Cite
|
Sign up to set email alerts
|

Falsely high ankle-brachial index predicts major amputation in critical limb ischemia

Abstract: Falsely high ankle-brachial index (ABI) values are associated with an adverse clinical outcome in diabetes mellitus. The aim of the present study was to verify whether such an association also exists in patients with chronic critical limb ischemia (CLI) with and without diabetes. A total of 229 patients (74 ± 11 years, 136 males, 244 limbs with CLI) were followed for 262 ± 136 days. Incompressibility of lower limb arteries (ABI > 1.3) was found in 45 patients, and was associated with diabetes mellitus ( p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 28 publications
3
52
1
1
Order By: Relevance
“…8,9 In a series of patients with PAD, with and without diabetes, an ABI > 1.3 increased amputation rates in both groups in a similar fashion. 22 Studies on the association between TP and patient outcome are scarce. A few studies have demonstrated the predictive effect of TBI on cardiovascular mortality and morbidity, irrespective of the diabetic status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In a series of patients with PAD, with and without diabetes, an ABI > 1.3 increased amputation rates in both groups in a similar fashion. 22 Studies on the association between TP and patient outcome are scarce. A few studies have demonstrated the predictive effect of TBI on cardiovascular mortality and morbidity, irrespective of the diabetic status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, medial calcification does not necessarily cause arterial stenosis and reduced blood flow [8,9,18]. The exclusion of patients with incompressible arteries (defined by an ABI ≥1.3), a factor known to be associated with poorer outcome in patients with limb ischaemia, in a number of published studies makes it increasingly difficult to evaluate its diagnostic utility [12,22]. In contrast, detection of a triphasic pedal Doppler arterial waveform with a handheld Doppler appears to provide stronger evidence for the absence of PAD.…”
Section: Rationalementioning
confidence: 99%
“…Evaluation of the macrocirculation using measurements of ankle-brachial index and ankle pressure can be falsely elevated because of excessive calcification of the tibial artery 21 and does not reflect blood flow below the ankle. With the limited use of macrocirculation assessment, intense evaluation of the microcirculation is essential in the setting of CLI.…”
Section: -13mentioning
confidence: 99%